Age-Related Difference in Functional Brain Connectivity of Mastication - Lin, Chia-shu; Wu, Ching-yi; Wu, Shih-yun; Lin, Hsiao-Han; Cheng, Dong-hui; Lo, Wen-liang (Frontiers in Aging Neuroscience, 2017)
Age-related decline in motor function is associated with changes in intrinsic brain signatures. Here, we investigated the functional connectivity (FC) associated masticatory performance, a clinical index evaluating general masticatory function. Twenty-sex older adults (OA) and 26 younger (YA) healthy adults were recruited and assessed for masticatory performance index (MPI) and resting-state functional magnetic resonance imaging (rs-fMRI). We analyzed the rs-fMRI FC network related to mastication, which was constructed based on 12 bilateral mastication-related brain regions according to literature. For the OA and the YA group, respectively, we identified the mastication-related hub, i.e., the node which degree centrality (DC) was positively correlated with MPI. For each pair of nodes, we identified the inter-nodal link which FC was positively correlated with MPI. The network analysis revealed that, in the YA group, FC between the sensorimotor cortex, the thalamus and the cerebellum is positively correlated with MPI. Consistently, the cerebellum nodes were found as the mastication-related hubs. In contrast, in the OA group, we found a sparser connection within the sensorimotor regions and cerebellum, and a denser connection across distributed regions, including the FC between the superior parietal lobe, the anterior insula, and the dorsal anterior cingulate cortex. Compared to the YA group, the OA group also comprised more mastication-related hubs, which were spatially distributed outside the sensorimotor regions, including the right superior parietal lobe, the right anterior insula, and the bilateral dorsal anterior cingulate cortex. In general, the findings supported the hypothesis that in the older adults, higher masticatory performance would be associated with a widespread pattern of the mastication-related hubs. Such a widespread engagement of multiple brain regions associated with MPI may reflect an increased demand in sensorimotor integration, attentional control and monitoring for the older adults to maintain good mastication.